Risk Analysis of Food Retail Companies in Hungary’s Northern Great Plain Region - Tarnóczi, Tibor; Fenyves, Veronika (International Journal of Engineering and Management Sciences, 2017)
Based on the financial ratios of analyzed companies we were performed a risk analysis, highlighting the degree of operational and financial leverages and the degree of combined leverage combining preceding ratios. We introduced a new aspect of the risk concept which began to spread in recent times. In the interest of to be able to analyse together cross-sectional and time series data, panel regression model was used. The panel regression is an extension of the multivariate linear regression interpreted as a multi-level model. In our study, the panel regression was used for analysis of food retailer companies, in the Northern Great Plain region's counties, in the period 2009-2014.